2018
DOI: 10.1021/acs.cgd.8b00765
|View full text |Cite
|
Sign up to set email alerts
|

Successful Computationally Directed Templating of Metastable Pharmaceutical Polymorphs

Abstract: A strategy of using crystal structure prediction (CSP) methods to determine which, if any, isostructural template could facilitate the first crystallization of a predicted polymorph by vapor deposition is extended to the fenamate family. Mefenamic acid (MFA) and tolfenamic acid (TFA) are used as molecules with minimal chemical differences, whereas flufenamic acid (FFA) shows greater differences in the substituents. The three crystal energy landscapes were calculated, and periodic electronic structure calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 62 publications
(103 reference statements)
3
94
0
Order By: Relevance
“…Tolfenamic acid (TFA; 2-[(3-chloro-2-methylphenyl)amino]benzoic acid; C 14 H 12 ClNO 2 ) is a non-steroidal anti-inflammatory drug (NSAID). It is frequently used as a model for crystallography studies because it displays interesting polymorphism, with eight forms identified to date (Andersen et al, 1989;Ló pez-Mejías et al, 2009;Case et al, 2018). Moreover, its small size and simple crystal structures permit timely computational calculations, which is advantageous for studies investigating its behaviour by nuclear magnetic resonance (NMR).…”
Section: Chemical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolfenamic acid (TFA; 2-[(3-chloro-2-methylphenyl)amino]benzoic acid; C 14 H 12 ClNO 2 ) is a non-steroidal anti-inflammatory drug (NSAID). It is frequently used as a model for crystallography studies because it displays interesting polymorphism, with eight forms identified to date (Andersen et al, 1989;Ló pez-Mejías et al, 2009;Case et al, 2018). Moreover, its small size and simple crystal structures permit timely computational calculations, which is advantageous for studies investigating its behaviour by nuclear magnetic resonance (NMR).…”
Section: Chemical Contextmentioning
confidence: 99%
“…A search for crystal structures containing TFA explicitly in its protonated state was performed within the Cambridge Structural Database (CSD version 5.41, update November 2019; Groom et al, 2016). There are eight polymorphs of pure TFA (CSD reference codes KAXXAI, KAXXAI01-07, Andersen et al, 1989;Ló pez-Mejías et al, 2009;Case et al, 2018) and six co-crystal forms (EXAQIE, Fá biá n et al, 2011; SIMDOK/01 & SIMFUS/SIMGAZ/SIMGED, Case et al, 2018; UZUZIA & UZUZOG, Bouanga Boudiombo & Jacobs, 2016; XOWKAX/01, Surov et al, 2015, Wittering et al, 2015. In all cases, the internal hydrogen-bond equvialent to N7-H7Á Á ÁO15 in the present structures is present and the hydroxyl hydrogen atom is attached to the corresponding O16 equivalent.…”
Section: Database Surveymentioning
confidence: 99%
“…A recently discovered form V of indomethacin was found to stabilize in nanoconfinement of the controlled porosity silica (Nartowski, Tedder, Braun, Fábián, & Khimyak, 2015). Metastable polymorphs of olanzapine (Warzecha et al, 2017), tolbutamide (Zhang et al, 2011) and mefenamic acid (Case et al, 2018) were also successfully crystallized using different heterosurfaces.…”
Section: Cuffini Et Al Elucidated the Crystallization Of Form II Of mentioning
confidence: 99%
“…Since degradation has been ruled out, the additional reflections must arise from a new polymorph of MA. In an attempt to identify this, predicted crystal structures were explored (Case et al, 2018). None of the low-energy structures provide a good match to the unassigned reflections (Fig.…”
Section: Figurementioning
confidence: 99%